Penerapan Laporan Keuangan Berbasis Standar Akuntansi Keuangan Entitas Mikro, Kecil, dan Menengah UMKM Sarabba Sucer BTP Makassar - Chairunnizah, Nur Ifani Putri; Arfah, Eka Ariaty; Arfah, Dwi Astuty; Alam, Syamsu (JOM, 2024)
The purpose of this study was to determine the application of financial report preparation at UMKM Sarabba Sucer BTP Makassar in accordance with the Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM). This research method begins with the problem identification stage, then a literature review is carried out, the next step is data collection using a mixed method. Primary data, namely interviews and secondary data collected from UMKM financial documents. After collecting data, researchers move on to the data analysis phase. The last step is to conclude the results of the study. The results of the study indicate that Sarabba Sucer has not fully implemented SAK EMKM in preparing their financial reports. The financial reports made are still simple and limited to manual recording without considering applicable standards. UMKM Sarabba Sucer managers should have an understanding of the concepts and principles of Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM) such as financial position reports, profit and loss reports, and notes to financial statements. It is recommended that UMKM Sarabba Sucer needs to get special training and support related to the implementation of SAK EMKM.